Coronary artery disease prevalence amongst patients undergoing valve replacement surgery: A South African perspective - Meel, Ruchika; Lohrmann, Graham M; Essop, Mohammed R (SA Heart Journal, 2018)
Background: The prevalence of coronary artery disease (CAD) amongst patients presented for valve surgery has important implications for routine angiography. Information on the frequency of CAD in predominantly black patients presented for valve surgery in South Africa has not been published. Methods: A retrospective, descriptive study of 116 patients presented for valve surgery that underwent coronary angiography between 2010 and 2011 was performed. CAD was defined as stenosis of 70% or greater in one or more epicardial vessels or ≥50% in the left main coronary artery, as defined by quantitative coronary angiography. Results: Median age was 57.4 (IQR 43 - 67) years (56.9% females). Black patients represented 66.4%, whites 19.8%, and, coloured and Indian patients 13.8%. Hypertension and smoking were the most common cardiovascular risk factors (26.7% and 16.4% respectively). Diabetes mellitus, dyslipidaemia, chronic kidney disease and prior CAD occurred collectively in 15.5% of study subjects. HIV prevalence was 12%, half of whom were on antiretroviral therapy. An isolated valve lesion occurred in 69% of patients, with the remainder having 2 or more lesions. The most common valve lesion was aortic stenosis (43.1%), followed by mitral stenosis (36.2%), aortic regurgitation (29.3%), mitral regurgitation (25.9%) and tricuspid regurgitation (19%). The predominant aetiology was rheumatic heart disease (58.6%), followed by degenerative valve disease (24.1%). CAD was documented in 10 patients (8.6%), of whom 8 had single vessel disease and 2 had double vessel disease. Conclusion: The low prevalence of CAD found in younger, asymptomatic black patients without cardiovascular risk factors referred for valve surgery, raises the question of whether routine pre-operative coronary angiography in this sub-group is appropriate.